The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/srin.202000394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ce Addition on Inclusions and Grain Structure in Gear Steel 20CrNiMo

Abstract: Through laboratory experiments and thermodynamic calculation, the chemical composition and morphology of inclusion and grain size in the cast melt are comprehensively characterized herein. The results show the evolution of Al2O3 inclusion formed by Al deoxidation in the gear steel 20CrNiMo follows the route of Al2O3 → CeAlO3 → Ce2O2S → Ce2O2S + CeS, and thus the nucleation core of complex CemnS sulfides changes from CeAlO inclusion to CeOS inclusion with the increase in Ce addition. Moreover, grain size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 24 publications
(23 reference statements)
0
21
0
Order By: Relevance
“…The Al 2 O 3 inclusion core reduced and even disappeared, and the thickness of LaAl 11 O 18 increased as the reaction proceeded. As the reaction time increased, LaAl 11 O 18 reacted with the dissolved La and transformed to LaAlO 3 , based on Equation (5), as shown in Figure 5 and 6. LaAl 11 normalO 18 + 5 [ La ] = 6 LaAlO 3 + 5 [ Al ] [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Al 2 O 3 inclusion core reduced and even disappeared, and the thickness of LaAl 11 O 18 increased as the reaction proceeded. As the reaction time increased, LaAl 11 O 18 reacted with the dissolved La and transformed to LaAlO 3 , based on Equation (5), as shown in Figure 5 and 6. LaAl 11 normalO 18 + 5 [ La ] = 6 LaAlO 3 + 5 [ Al ] [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 9–12 ] The formation and modification of inclusions after the addition of Ce have been extensively studied. [ 13–16 ] Luo and Pan et al [ 17,18 ] reported that CeAl 11 O 18 and CeAlO 3 inclusions, respectively, were detected after adding Ce to gear steel and Al‐killed austenitic stainless steel. Ren and Zhang [ 19 ] concluded that the evolution route of the inclusions was Al 2 O 3 → CeAlO 3 → Ce 2 O 2 S → Ce 2 O 2 S + CeS, with a Ce addition from 0 to 0.028 wt% in an ultralow‐carbon Al‐killed steel.…”
Section: Introductionmentioning
confidence: 99%
“…The formation and modification of inclusions in steels have been widely investigated. [18][19][20][21][22][23][24][25][26][27] The thermodynamic equilibrium of Ce-O and Ce-O-S in the molten iron was studied. [28][29][30][31] Rare-earth elements had a strong affinity to oxygen and sulfur in the steel, [32] which could modify hard alumina [33,34] and elongated sulfides to rare-earth oxides or rare-earth oxy-sulfides.…”
Section: Introductionmentioning
confidence: 99%
“…There have been extensive studies on the modification of Al 2 O 3based inclusions by REMs. [23][24][25][26][27][28][29] Li [25] studied the effect of lanthanum on inclusion evolution in high-Al steel and concluded that the evolution route was Al 2 O 3 ! LaAl 11 O 18 !…”
Section: Introductionmentioning
confidence: 99%